NECESSIDADES DO CUIDADOR FAMILIAR DE CRIANÇAS E ADOLESCENTES COM DIABETES MELLITUS - Viégas, Cynthia Griselda Castro (2013)
The demands arising from the care of children and adolescents with the chronical condition of Diabetes can alter de dynamics of a family, especially of the family caregiver. From this process of care emerge needs related to the disease, as well as to the different aspects of Diabetes therapeutic and the human behavior. Thus, the Professional care must be embracing and multidimensional to identify needs and minimize worries, fears and anxiety of the caregiver and the affected child and / or adolescent. Delimited by such assertions are the following research problems: What needs are experienced by family caregivers from the demands of caring for a child or adolescent with diabetes? The investigated objective can take the nurse to understand many situations of care such as physical, psychic, affective and emotional aspects as well as the difficulties and worries that are presented to the family and to caregivers of children and adolescents with diabetes, in a dimension that reach the social practice of the nurse. The research had as an objective to understand the needs of the family caregiver of children and adolescents with diabetes. For that a descriptive exploratory research with qualitative approach with eleven family caregivers of children and adolescents was made, in the Program of Education for Diabetes in the Health center of Liberdade, in the city of São Luís, State of Maranhão. To collect the data it was used an open interview with data analysis from Theme Analysis. After the analytical-reflexive process concerning the data, the needs were grouped from a great simension of support to caregiving, and for the raw data analysis were grouped into three theme characteristics: Needs of Instrumental Support, Needs of Informative Support and Needs of Emotional Support. Among the needs of instrumental support, it is highlighted the difficulty of access for diagnose and treatment, financial support and the unpreparedness and lack of professional skills in managing diabetes; as need of informative support emerged the theme information for caregiving; among the needs of emotional support is it highlighted the changes in the family routine and support and the caregiving inside the familiar and school context. From the comprehension of the needs of the nurse, it is perceived the importance of the proximity of the nurse with the specificities of this caregiver, expanding the action focus to care and establishing actions that support the integrity and integrality of the family and the health-disease-care process.